Supply chain preparedness: How operational settings, product and disaster characteristics affect humanitarian responses - Jonas Stumpf; Maria Besiou; Tina Wakolbinger (Production and Operations Management, 2023)
Supply chains are dynamic and complex systems. This holds particularly true for humanitarian supply chains that operate under strong uncertainty. In view of an ever-growing gap of unmet humanitarian needs, it is essential to gain a better understanding of the behavior of humanitarian supply chain systems. Despite a growing academic output in this field, there is a lack of empirical studies that take an integrated view on humanitarian supply chains and support decision makers with fact-based evidence. Based on four extensive case studies and existing literature, we developed a system dynamics model that reflects the operational reality of humanitarian organizations in form of their centralized, hybrid and decentralized settings. The model provides a holistic supply chain view and measures the operational performance with regard to response cost, delivery lead time and impact on the local economy. Furthermore, we studied the impact of preparedness investments to enhance operational performance in the supply chain and deliver more humanitarian assistance with the limited resources available. Finally, we used our model to analyze the impact of major shocks such as the COVID-19 pandemic to assess the vulnerability of humanitarian supply chains. The results indicate that operational settings, product and disaster characteristics have a major influence on the supply chain performance both in the noninvestment case as well as in the case where preparedness investments have been made. Specifically, for low-value items, we find that decentralized settings have the lowest supply chain costs while for high-value items the price difference between local and international procurement determines which setting is the most cost-effective one. The preferability of the supply chain setting strongly depends on the indicator chosen. Hence, ultimately, the findings emphasize the need to apply appropriate indicators and identify their trade-offs to comprehensively analyze the performance of humanitarian supply chain settings. The newly introduced Humanitarian Return-on-Investment concept can play an important role in this context.
Keywords: 650; humanitarian supply chains; major shocks; operational reality; preparedness; return-on-investment; systemic thinking